Graft Survival, Graft Rejection, and Glaucoma in a Consecutive Series of Descemet Stripping Endothelial Keratoplasty. Issue 5 (20th May 2023) - Patel, Sanjay V.; Hodge, David O.; Winkler, Nelson S.; Maguire, Leo J.; Baratz, Keith H.
Abstract : Purpose: The goal of this study was to compare outcomes of Descemet stripping endothelial keratoplasty (DSEK) in eyes with glaucoma and abnormal anatomy to eyes with Fuchs endothelial corneal dystrophy (FECD). Methods: In a retrospective interventional series of all cases of DSEK between April 1, 2006, and November 30, 2015, recipient diagnosis, preoperative glaucoma status, concurrent surgical procedures, and graft outcomes were recorded. Graft survival, risk of rejection, and subsequent glaucoma surgery were estimated by using Kaplan–Meier analysis with risk factors determined by proportional hazard models. Results: Of 703 DSEKs in 666 eyes (509 subjects), the main recipient diagnoses were FECD (n = 496), pseudophakic corneal edema (n = 112), and failed graft (n = 83). Glaucoma was present in 150 cases before DSEK. Overall graft survival was 85%, 75%, and 71% at 5, 10, and 12 years, respectively, and for FECD without glaucoma was 95%, 89%, and 87% at 5, 10, and 12 years, respectively. Independent risk factors for graft failure included recipient diagnoses of pseudophakic corneal edema (HR = 8.3, P < 0.001), failed graft (HR = 6.4, P < 0.001), and preoperative medical glaucoma (HR = 7.1, P < 0.001) or surgical glaucoma (HR = 12.3, P < 0.001). Preoperative glaucoma treated by previous surgery resulted in graft survival of 28% at 10 years. Preoperative glaucoma was associated with an increased risk of graft rejection (HR = 6.8, P < 0.001) and subsequent glaucoma surgery (HR > 17.4, P < 0.001). Conclusions: Preoperative glaucoma increases the risk of graft failure, graft rejection, and needing subsequent glaucoma surgery in the first decade after DSEK. With previous glaucoma surgery, DSEK graft survival was more favorable compared with published reports of Descemet membrane endothelial keratoplasty.